Teaching trust in science: a critical new focus for science education - Hopkin, Karen; Roberts, Keith; Alberts, Bruce (Frontiers in Communication, 2025)
The recent pandemic has revealed the importance of understanding how scientific knowledge is produced, if citizens are to make decisions that protect themselves, their communities, and their nations. Creating such an understanding presents a critical and urgent challenge for the world’s education systems. In this essay, we propose that teachers prioritize producing an understanding of the scientific process at all levels of science education.